High‐Pressure Behavior and Phase Stability of Al5BO9, a Mullite‐Type Ceramic Material. Issue 8 (25th May 2013) - Gatta, G. Diego; Lotti, Paolo; Merlini, Marco; Liermann, Hanns‐Peter; Fisch, Martin; Wong‐Ng, W. K.
<x xml:space="preserve">Abstract</x> Phase stability, elastic behavior, and pressure‐induced structural evolution of synthetic boron‐mullite Al5BO9 (a = 5.6780(7), b = 15.035(6), and c =7.698(3) Å, space group Cmc21, Z = 4) were investigated up to 25.6(1) GPa by in situ single‐crystal synchrotron X‐ray diffraction with a diamond anvil cell (DAC) under hydrostatic conditions. No evidence of phase transition was observed up to 21.7(1) GPa. At 25.6(1) GPa, the refined unit‐cell parameters deviated significantly from the compressional trend, and the diffraction peaks appeared broader than at lower pressure. At 26.7(1) GPa, the diffraction pattern was not indexable, suggesting amorphization of the material or a phase transition to a high‐pressure polymorph. Fitting the P–V data up to 21.7(1) GPa with a second‐order Birch–Murnaghan Equation‐of‐State, we obtained a bulk modulus KT0 = 164(1) GPa. The axial compressibilities, here described as linearized bulk moduli, are as follows: KT0(a) = 244(9), KT0(b) = 120(4), and KT0(c) = 166(11) GPa (KT0(a):KT0(b):KT0(c) = 2.03:1:1.38). The structure refinements allowed a description of the main deformation mechanisms in response to the applied pressure. The stiffer crystallographic direction appears to be controlled by the infinite chains of edge‐sharing octahedra running along [100], making the structure less compressible along the a‐axis than along the b‐ and c‐axis.